Q: 9h-6 plus 12h plus 40 equals 22?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

h-9h-6+12h+40 = 22 h-9h+12h = 22+6-40 4h = -12 h = -3

-9h-6+12h+40 = 22 3h+34 = 22 3h = 22-34 3h = -12 h = -4

h= -4

-9h - 6 + 12h + 40 = 22 ie 3h = 22 + 6 - 40 h= -12/3 = -4

The solution to this equation is that h is equal to -4. You can substitute this value for h into the equation to get -4 x -9 - 6 plus 12 x -4 plus 40 equals 22, or 36 - 6 plus - 48 plus 40 equals 22.

Related questions

-9h-6+12h+40=22

-9h-6+12h+40=22 -9h+12h=22-40+6 3h=-12 h=-4

h-9h-6+12h+40 = 22 h-9h+12h = 22+6-40 4h = -12 h = -3

-9h-6+12h+40 = 22 3h+34 = 22 3h = 22-34 3h = -12 h = -4

h= -4

-9h - 6 + 12h + 40 = 22 ie 3h = 22 + 6 - 40 h= -12/3 = -4

The solution to this equation is that h is equal to -4. You can substitute this value for h into the equation to get -4 x -9 - 6 plus 12 x -4 plus 40 equals 22, or 36 - 6 plus - 48 plus 40 equals 22.

-9h - 6 + 12h + 40 = 22, simplifying this gives12h - 9h + 40 - 6 = 223h + 34 = 22, taking 34 off both sides gives3h + 34 - 34 = 22 - 343h = -12, thush = -12/3 = -4

If you're trying to find h... -9h - 6 + 12h + 40 = 22 3h = -12 h = -4 If you're not trying to find h... You're question makes no sense. When asking a question, try to define something for a person to answer.

22+22+28+28=100.

2

22